(untitled) (Research, Society and Development, 2021)
Integrated agricultural production systems can improve the physical, chemical and biological quality of the soil. Obtaining synergistic effects between the different production components allows the sustainability of the agropastoral, silvopastoral, agroforestry and agrosilvopastoral systems. Increases in carbon storage can be obtained with the adoption of integrated production systems, in addition to greater economic returns. The diversification of production makes it possible to reduce risks in the face of fluctuations in market prices. However, studies involving carbon storage and, mainly, the economic viability of integrated systems in the semiarid region are limited. In this context, the objective was to present results of carbon storage and economic return obtained with the adoption of integrated production systems in the semiarid region, aiming to present results that can subsidize the implementation of future projects, allowing to obtain gains in carbon stocks and greater economic viability in conditions of low water availability.